Evaluasi Pengembangan Wilayah Permukiman Berdasarkan Pemetaan Kerusakan Permukiman Akibat Banjir Lahar Di Kali Putih, Kabupaten Magelang - Rosalina Kumalawati; Seftiawan Samsu Rijal; R Rijanta; Junun Sartohadi; Rimawan Pradiptyo (TATALOKA, 2013)
The aim of this study are (1) to assess the damage of settlement due to lahar flood in study area, (2) to analyze the damage of settlement and (3) to analyze the allocated space of settlement development based on classification of damage settlement. Methods that used in this study are GPS Tracking to know the distribution of lahar flood, classification of damage settlement based on predetermined criteria and spatial autocorrelation to know the pattern of damage settlement. The result of this study is showing that damage settlement due to lahar flood is not only caused by the house distance to the river but also by the materials of it. The spatial pattern of damage settlement is 0,68 (clustered) for Collapse, 0,62 (clustered) for High Damaged, 1,05(clustered) for Low Damaged, 0,64 (clustered) for Medium Damaged) and 1,21 (clustered) for No Damaged.